Totally endoscopic mitral valve repair with novel technique of left atrial exposure: five years experience from a single center - Thanh Dat Pham; Thanh Huyen Tran; Ngoc Thanh Le; Cong Huu Nguyen (Journal of Cardiothoracic Surgery, 2025)
Abstract Background .Endoscopic mitral valve repair has progressively been adopted as the standard approach for treating isolated mitral regurgitation across numerous renowned cardiac surgery centers worldwide. Our innovative method for mitral valve exposure has been previously described. This study evaluates the outcomes of totally endoscopic mitral valve repair using this advanced technique over a five-year period at a single center. Methods . A retrospective review was conducted on 122 patients who underwent totally endoscopic mitral valve repair between May 2018 and December 2023. Clinical and echocardiographic data were meticulously collected and analyzed. The surgical procedure was performed completely endoscopic via a 3–4 cm right mini-thoracotomy, with peripheral cardiopulmonary bypass. A specialized technique utilizing retraction sutures for mitral valve exposure was employed. Primary outcomes included the results of the endoscopic techniques, mitral valve repair outcomes, perioperative complications, and short-term mortality. Long-term outcomes, including survival, freedom from reoperation, and recurrent mitral regurgitation, were assessed using Kaplan–Meier analysis. Results . Mitral valve exposure was successfully achieved in all cases. The mean age of the patients was 54.5 ± 14.2 years, and their mean log EuroSCORE II was 1.53 ± 1.30. The repair rate was 96%, with anterior leaflet repair in 13%, posterior leaflet repair in 69%, and bileaflet repair in 14%. Mean aortic cross-clamp time and cardiopulmonary bypass time were 117 ± 39 min and 181 ± 48 min, respectively. The early mortality rate was 1.6%. Three patients (2.5%) experienced intraoperative conversion to sternotomy and 6 patients (4.9%) underwent a reoperation. There were 2 cases of stroke (1.6%) and 2 cases of unilateral pulmonary edema (1.6%). The minimum follow-up duration for a patient was 6 months, extending up to 72 months, with a mean follow-up duration of 28.6 ± 15.1 months. Kaplan–Meier analysis demonstrated a 96.7 ± 1.6% survival rate at 5 years, with 98.4 ± 1.2% freedom from reoperation, and 86.1 ± 3.1% freedom from recurrent mitral regurgitation. Conclusions . Totally endoscopic mitral valve repair utilizing the novel technique of left atrial exposure is feasible and can be safely performed with low mortality and morbidity. This approach achieves a high rate of mitral repair and demonstrates favorable long-term outcomes.